Aesthetic Facial Surgery: Contribution from the Anterior Mandible Osteotomy (International Journal of Medical and Surgical Sciences, 2014)
Facial aesthetic surgery has been modified in the last 15 years. Different procedures and soft/hard tissue facial surgeries realized concurrently allow surgeons to achieve demanding aesthetics targets. The aim of this paper is to show variations in the osteotomy of symphyses and parasymphyses mandible to obtain better esthetic results. A series of four patient cases is presented to analyze the surgical procedure, using a segmental osteotomy of the anterior mandible, median osteotomy of the mandible, and a combination of these procedures. The results show a versatility of these technique and new target with good esthetic results can be used. In conclusion, variations of the osteotomy in the anterior area of the mandible are used according to individual requirements of each case, and can be performed with a low morbidity.